Argentina's missing bones : revisiting the history of the dirty war - Brennan, James P., 1955- (Violence in Latin American history, 2018)
"Argentina's missing bones: revisiting the history of the dirty war examines the history of state terrorism during Argentina's 1976-83 military dictatorship in a single place: the industrial city of Córdoba, Argentina's second largest city and the site of some of the dirty war's greatest crimes. It examines the city's previous history of social protest, working-class militancy, and leftist activism as an explanation for the particular nature of the dirty war there. Argentina's missing bones examines both national and transnational influences on the counter-revolutionary war in Córdoba. The book also considers the legacy of this period and examines the role of the state in constructing a public memory of the violence and holding those responsible accountable through the most extensive trials for crimes against humanity to take place anywhere in Latin America"--Provided by publisher.